INFORMATION AND COMMUNICATION TECHNOLOGY IN ORGANIZATION OF EXTRACURRICULAR WORK WITH GIFTED STUDENTS IN THE SYSTEM OF THE LITERARY EDUCATION - Ольга Петрович (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with the issue of features of the use of information and communication technology in organizing extra-curricular activities with the literary gifted students. Main attention is drawn on the effective forms and methods of information and communication technology for the successful conduction of extracurricular activities with gifted high school students in literary education system, in particular such as: web quests, QR-codes, QR-quests, Google Groups, multimedia presentations, blogging, virtual tours, use of interactive whiteboards, educational forums, databases educational resources, virtual libraries, creating the electronic portfolio, media library of educational material, comics, doodles, clouds of words etc.